Safety of ustekinumab or vedolizumab in pregnant inflammatory bowel disease patients: a multicentre cohort study. Issue 4 (7th December 2020) - Wils, Pauline; Seksik, Philippe; Stefanescu, Carmen; Nancey, Stephane; Allez, Matthieu; Pineton de Chambrun, Guillaume; Altwegg, Romain; Gilletta, Cyrielle; Vuitton, Lucine; Viennot, Stéphanie; Serrero, Mélanie; Fumery, Mathurin; et al.
Summary: Background: The prevalence of inflammatory bowel diseases (IBD) is high in women of childbearing age. Achieving clinical remission from conception to delivery using current medications is a major issue in IBD. Aims: To assess maternal and neonatal complications and management of vedolizumab or ustekinumab) in pregnant women with IBD receiving these agents. Methods: We performed a retrospective cohort study among GETAID centres including women with IBD who received ustekinumab or vedolizumab during pregnancy or within the 2 months before conception and compared outcomes to women exposed to anti‐TNF treatment during pregnancy. Results: Seventy‐three pregnancies in 68 women with IBD were analysed: 29 on ustekinumab resulting in 26 (90%) live births, two (7%) spontaneous abortions and one (3%) elective termination; 44 on vedolizumab resulting in 38 (86%) live births, five (11%) spontaneous abortions and one (3%) medical interruption. The control group included 88 pregnancies exposed to anti‐TNF in 76 women with IBD. The median age at conception, the proportion of women who smoked or in clinical activity at conception was comparable between groups. Only the proportion of patients exposed to >2 anti‐TNF agents was significantly increased among the ustekinumab and vedolizumab groups compared to control group (22% and 10% vs 3%, P < 0.005). Rates of prematurity, spontaneous abortion, congenital malformations and maternal complications were comparable between groups. Conclusion: We report 73 pregnancies in patients receiving vedolizumab or ustekinumab without a negative signal on maternal or neonatal outcomes. Further prospective studies are needed on the outcomes of pregnancies with new biologic drugs.